We Created Chávez : A People's History of the Venezuelan Revolution - Ciccariello-Maher, George (Book collections on Project MUSE., 2013)
Introduction: what people? whose history? -- A guerrilla history -- Reconnecting with the masses -- Birth of the "Tupamaros" -- Interlude : the Caracazo : history splits in two -- Sergio's blood: student struggles from the university to the streets -- Manuelita's boots : women between two movements -- Jose Leonardo's body and the collapse of mestizaje -- Interlude : every 11th has its 13th -- Venezuelan workers : aristocracy or revolutionary class? -- Oligarchs tremble! : peasant struggles at the margins of the state -- A new proletariat : informal labor and the revolutionary streets -- Conclusion : dual power against the magical state.